A capacitive proximity sensing scheme for human motion detection - Arshad, Atika; Khan, Sheroz; Alam, A. H. M. Zahirul; Abdul Kadir, Kushsairy; Tasnim, Rumana; Ismail, Ahmad Fadzil (IEEE, 2017)
This work demonstrates a non-invasive capacitive proximity based floor sensing system to monitor the motion of a human body (elderly patients). Monitoring the motion of an elderly patient can help them to move freely without the limitation of staying in a restricted environment which is suited for homecare applications. On the basis of application, such implementations need low-power, accurate and real-time measurement for measuring any abnormal behaviours. The proposed capacitive sensing system is based on the idea of making capacitive variations due to human body motion and this variation in capacitance is converted into an equivalent signal that has proportionate output frequency change. The floor sensor is proposed to be employed underneath the carpets of the floor surface. The sensors are rectangular shaped electrodes, arranged in the form of a matrix.